Philosophy of the Name. - Bulgakov, Sergii (Lightning Source Inc. (Tier 3) : Northern Illinois University Press, 2022)
"By subjecting the simple sentence "A is B" to a grammatical and philosophical analysis, Sergii Bulgakov develops a philosophy of words and names and demonstrates that the Name-glorifiers' claim that the "Name of God is God" is susceptible of an orthodox understanding"--